Care Sched: Doctor and Patient Appointment Management - Poornima Nayak; Mohammad Ziaullah; Tabasum Guledgudd (International Journal of Computer Science Languages, 2025)
The medical appointment system is a web application that uses PHP, JavaScript, and CSS to improve the efficiency of booking medical appointments. It features two interfaces: an admin side where patients and doctors manage their appointments and a user side where they may handle an appointment and to view records, and manage their medicines. The web platform that the system makes available provides a convenient online experience from any internet-enabled device, facilitating appointment scheduling, reducing errors, and lowering administrative workload. The shortcomings of traditional scheduling methods are addressed by this system, which increases accessibility and simplifies operations for healthcare management. The doctor appointment system tackles two main concerns with traditional appointment booking methods: lengthy wait times and human scheduling challenges. Using web technologies to create an intuitive interface for user and administrative interactions, this system seeks to speed up the appointment process. Physician and patient records are managed by the admin side of the system, while medication management, appointment scheduling, and treatment histories are accessible through the user side. This approach enhances both customer satisfaction and operational efficiency.
Keywords: JavaScript; admin; medical appointment